Psychometric Characteristics of the Brazil Mood Scale among Youth and Elite Athletes Using Two Response Time Frames - Izabel Cristina Provenza de Miranda Rohlfs; Franco Noce; Tim J. Gabbett; Carolina Wilke; Marcelo Vido; Victoria R. Terry; Peter C. Terry (MDPI AG, 2023)
Regular assessment of the mood construct as an indicator of psychological wellbeing is used in Brazil to screen athletes for risk of mental health issues. The present study tested the psychometric characteristics of the Brazil Mood Scale (BRAMS) using both "right now" and "past week" response time frames and investigated between-group differences in mood based on athletes' sex, age, and social vulnerability. Participants were 898 athletes (511 male, 387 female, age range: 12-44 years) from eight sports. The factorial validity of the BRAMS was supported using both response time frames independently and in a multi-sample analysis. Subscale reliability was supported for both time frames. Fatigue, depression, and tension scores were higher using the "past week" time frame than the "right now" time frame. Males reported higher vigor scores than females, and younger participants (<18 years) reported lower scores for anger and depression than older participants (18+ years). No significant differences in mood (p > 0.05) were found between participants identified as socially vulnerable and those who were not socially vulnerable. Findings supported the psychometric integrity of the BRAMS and its use as a screening measure for psychological wellbeing among youth and elite athletes in Brazil.